Housing Quality and Perceived Health Effects in Ijebu Ode, Nigeria - OTTO, Edet; OGUNYEMI, Kayode; LUYI, Oluwasina (International Journal of Advances in Life Science and Technology, 2022)
Despite the mounting compendium of scientific evidence that has clearly documented the link between poor housing quality and health both locally and globally, poor housing quality has continued to be a significant concern in public health, especially in rural and sub-rural areas of emerging nations like Nigeria, where there is slight or no knowledge about the public health consequences of poor housing quality. As a result, the object of this work is to observe the housing quality and the perceived health impacts in Ijebu Ode, Nigeria. The work adopted a descriptive but cross-sectional approach, and data was obtained from four hundred (400) systemically sampled households through structured questionnaires, and analysed descriptively using a statistical tool for social scientists. According to the findings, a significant number of the residents 51.5% had no water in their houses, 44% had two windows in the room; out of which only 32% had windows on the two walls of the room, and 33% of the homes were overcrowded with over two people in a room. The findings further revealed that the vast majority of residents reported having cases of malaria with 67.5%, and cases of typhoid and cough with 15.5% and 4.5%, respectively. Consequently, the study has hitherto concluded that housing quality in Ijebu Ode is poor, which is a major predictor of the perceived health effects experienced by the residents.